Teacher transformation: a transformative learning perspective - Taylor, Edward W. (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
Fostering teacher transformation, change in beliefs about teaching, is a significant challenge in the education of teachers. This paper explores teacher transformation, from the theory of transformative learning with a specific focus on growing interest in the practice of fostering transformative learning. In response to this interest this paper takes a critical perspective of fostering transformative exploring the role and implications of essential four constructs: critical reflection, experience, empathy and relationships and what they mean for the practice of fostering transformative learning and teacher transformation.